Conflitos ambientais e de pesca: o caso do rio Arari e a regulamentação do acordo de pesca - Dias, Bianca Gabriela Cardoso (2012)
Since the establishment of the Social Contract that Rousseau spoke, society agreed to leave individualism to legitimize a transcendental entity, the State, to regulate its dynamics, being able to edit this normative elements that regulate the community life in order to achieve estimated as the social peace. Occurs that, although the theory of the State so dictate, in many cases the state entity cannot cover the variety of situations that are presented by social life, especially in those countries with continental dimensions like Brazil, especially in the Amazon region. However, it is not only this factor that presents itself as a barrier to access by state agencies, but also an unique feature of the area: the great cultural diversity. It is known that the most isolated regions of the Amazon, especially in the state of Amazon have their own normative systems, far from the state approval, but practiced fully by community members, regardless of whether such Community rules go against the national legal system or not. In this sense, becomes important to perform a study on the possible conflict between the local customary law and national law, tracing outlines about its occurrence and verifying actual cases experienced by communities that live their lives there. With this in mind, this study will focus on the looks for issues relating to conflicts of fishing tools used by fishing communities to regulate local and regional interests, allowing the management of natural resources in order to contemplate the reality experienced by coastal communities, specifically contemplating the case of Arari River, passing from the formation process of formalization of the agreement, reaching its effective results in the community.